Anti-inflammatory activity of cinnamon (C. zeylanicum and C. cassia) extracts – identification of E-cinnamaldehyde and o-methoxy cinnamaldehyde as the most potent bioactive compounds. Issue 3 (11th March 2015) - Gunawardena, Dhanushka; Karunaweera, Niloo; Lee, Samiuela; van Der Kooy, Frank; Harman, David G.; Raju, Ritesh; Bennett, Louise; Gyengesi, Erika; Sucher, Nikolaus J.; Münch, Gerald
<x xml:space="preserve">Abstract</x> The main inflammatory compounds in cinnamon are E-cinnamaldehyde and o-methoxy cinnamaldehyde.